Pengaruh Motivasi, Kepemimpinan Dan Kedisiplinan Terhadap Kinerja Pegawai (Studi Kasus Pada Dinas Pendapatan, Pengelolaan Keuangan Dan Asetdaerah Wonogiri) - Utari, Utari, Drs. Suyatmin Waskito Adi, M.Si (2015)
This research purposes to analysis motivation, leadership and discipline influence to job performance at Institute management, financial income and asset local of Wonogiri. This research uses quantitative method with primary data by questionnaire. Population of this research is employees institute management, financial income and asset local of Wonogiri. Sum samples are 26 respondents. Collecting sample method uses convenience sampling technique. Analysis tools uses validity and reliability test, normality test, multicolinierity test, heteroscedasticity, regression linier test, F test, coefficient determination R² test and t test. Base on analysis data result conclusions variable motivation is significant influences to job performance that shows by significant value is 0.001 < α s H1 receive with significant value (0.001<0.05). While leadership variable is not significant influence to job performance. That shows significant value 0.382 > α. So H2 reject with significant level (0.382 > 0.05). Discipline variable is not significant influence to job performance. That shows significant value is 0.134 > α so H3 reject significant level (0.134 > 0.05). Keyword: motivation, leadership, discipline and job performance.